Noun-Forming Suffix Found in Football News - Wea, Igrida Septiana; I G B Wahyu Nugraha Putra (Institut Agama Islam Negeri Palopo, 2024)
This research analyzed the types of noun-forming derivational suffixes found in football news articles. The document method is used to collect data, qualitative analysis to identify the dominant types of suffixes and their context of use, while quantitative analysis to determine the frequency of suffix usage. These methods provide a comprehensive understanding of noun-forming suffixes, taking into account meaning and accurate data. This research used the theory proposed by Hamawand (2011) and the supporting theory from Lieber (2009). A total of 221 data of noun-forming suffixes were found, with 156 (70%) verbal root data, 46 (21%) adjective root data, and 19 (8%) nominal base data. The analysis shows that verbal root suffix is the most common type of noun-forming suffix found in football news. The dominance is because of the use of verbs that describe an activity or action in the match involving the team or players in the match. Although verbal root only has five suffixes, but it dominates in football news texts.